Analysis Of Insect Fauna Biodiversity On Reclamation Land From Former Nickel Mining In Konawe Regency - Awaluddin Awaluddin; Ibnu Fajar; Muhammad Botek; Waode Siti Anima Hisein; Nuriadi Nuriadi; Siska Efendi (Fakultas Teknologi Pertanian Unsultra, 2026)
Nickel mining activities have been identified as a factor in insect biodiversity degradation. This study aimed to evaluate insect community parameters, including species, diversity, abundance, and evenness, by comparing post-mining and natural land in Amonggedo District, Konawe Regency. Sampling was conducted using sweep net, pitfall trap, and light trap methods. The findings showed a significant decrease in species richness in the post-mining land (4 orders, 6 families, 11 individuals) compared to the control land (6 orders, 11 families, 104 individuals). Although both locations had a moderate diversity index (H’) (1.55 vs. 1.72), the post-mining land recorded a higher evenness index (E) (0.86), indicating a more balanced distribution between families but with a much lower population. Dominance shifted from Ectobiidae in the natural land to Crambidae and Scoliidae in the post-mining area, confirming a transformation in community structure due to the impact of nickel mining.